2023
DOI: 10.1002/cam4.5725
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hope at diagnosis: A study among Guatemalan parents of children with cancer

Abstract: Background In high‐income countries, hope facilitates parental coping and builds the clinical relationship between families of children with cancer and their clinicians. However, the manifestation of hope in low‐ and middle‐income countries (LMICs) remains poorly understood. Our study explores Guatemalan parents' experiences with hope during the pediatric oncology diagnostic process and aims to identify discrete actions clinicians take to support hope. Methods This qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…A qualitative study conducted among 20 parents of children with cancer revealed that the establishment of hope had a profound impact on parents at both the emotional and cognitive levels. This hope was found to improve the parents’ overall mood, foster greater acceptance of the reality they were facing, and empower them to effectively care for themselves and their children ( Williams et al, 2023 ). However, the possible links between hope and positive emotions have not yet been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study conducted among 20 parents of children with cancer revealed that the establishment of hope had a profound impact on parents at both the emotional and cognitive levels. This hope was found to improve the parents’ overall mood, foster greater acceptance of the reality they were facing, and empower them to effectively care for themselves and their children ( Williams et al, 2023 ). However, the possible links between hope and positive emotions have not yet been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%